O uso do IVDN no estudo da degradação ambiental de bacias hidrográficas do litoral sul do estado da Paraíba - Lucena, Alysson Pereira de (2014)
This work aims the implementation of the Index Normalized Difference Vegetation (NDVI) in the study of environmental degradation of watersheds of rivers and river Gramame Abiai-Papocas, both located on the south coast of Paraíba state. The survey was conducted from images of Landsat 5 TM satellite, the years 1989, 2001 and 2006. Initially Atmospheric and radiometric corrections were performed. From the corrected images extracted and it was made thematic maps tracks the NDVI, which highlighted the density of vegetation cover. Then on-site visits, in which sampling points chosen as representative in supervised classification by regions, satellite images, which resulted in the preparation of thematic maps of land use were collected were performed. Topographic information from the Digital Elevation Model (DEM) images The Shuttle Radar Topography Mission (SRTM) thematic maps describing the ground from the height of each pixel in the drainage network relationship were made using the algorithm Height Above the Neareast Drainage (HAND). Then crosses the NDVI data with land use and with the HAND were carried out to justify the responses of NDVI, as well as evaluating its relationship with the land uses and the gap compared the drainage network. From the intersection of NDVI with HAND verified the presence of vegetation with greater biomass in the lower regions. With the crossing of the maps of land use and NDVI was observed that a large number of areas with exposed soils showed NDVI values in the range of -0.25 to 0.15. As for vegetation degradation in river basins, there was a decrease in NDVI values for 2001 and 1989 regeneration 2001 for 2006 observed an increasing convergence of natural vegetation in farmland and urban expansion without planning.; and that much of the degradation are derived from the practice of mining and farming without the use of soil conservation techniques. It was also found that data obtained in research enabled the generation of information that can be used in other research and aid decision makers in formulating geared to minimizing the environmental degradation in the watersheds studied public policy